Varenicline treatment for smoking cessation in high risk patients: a budget impact analysis - Spandonaro, Federico; Mancusi, Letizia; Polistena, Barbara (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
INTRODUCTION: The promotion of smoking cessation is a worldwide Public Health priority.OBJECTIVE: To estimate the budget impact on the Italian National Health Service (NHS) of the access to reimbursement of varenicline for the treatment of high risk patients with bronchopulmonary, diabetic and cardiovascular diseases.METHODS: A closed-group Markov model was developed in order to compare the costs incurred by the NHS to promote smoking cessation with cessation-related savings, using an alternative scenario in which aids to cessation are not reimbursed by the NHS. The analysis was conducted over a 5-year time horizon, in the perspective of the Italian NHS. Efficacy was expressed in terms of smoke abstinence for at least one year, and data was derived from clinical trials; the savings associated with smoking cessation were derived from cost-of-illness studies.RESULTS: The results show how costs would concentrate in the first year: they are estimated at € 200.6 million, of which € 162.4 million for drug therapy and € 38.2 million for counseling. Average annual savings over the first five years are estimated at € 77.7 million, with a cumulative net impact at 5 years of € -188.0 million (cost-saving). The analysis appears to be robust: sensitivity analyses show that the covering of initial costs occurs in any case between the third and fourth year, and that the treatment remains cost-saving at 5 years.CONCLUSIONS: The financial impact on the Italian NHS of the reimbursement of varenicline for the treatment of high risk smoking population would be a sustainable healthcare policy, resulting in cost savings starting from the fourth year.